2014
DOI: 10.1007/s10554-014-0420-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of coronary CT angiography on long-term follow-up of 6.9 years

Abstract: Long term follow-up of coronary CT angiography (CCTA) is scarce. The aim of the present study was to assess the prognostic value of CCTA over a follow-up period of more than 6 years. 218 Patients were included undergoing 64-slice CCTA. Images were analysed with regard to the presence of nonobstructive (<50 %) or obstructive (50 % stenosis) coronary artery disease (CAD). Major adverse cardiovascular events (MACE) were defined as death, nonfatal myocardial infarction or urgent coronary revascularization. CCTA re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 20 publications
5
18
1
2
Order By: Relevance
“…50 Their results are in line with these reports highlighting the excellent longterm prognosis in normal CCTA with a very low likelihood for cardiac events. Two systematic reviews/meta-analyses on the prognostic value of CCTA also confirmed these findings with low cumulative major adverse cardiac events in patients with normal CCTA findings, but much higher event rates in patients with abnormal CCTA showing obstructive CAD.…”
Section: Limitations Of Cctasupporting
confidence: 83%
“…50 Their results are in line with these reports highlighting the excellent longterm prognosis in normal CCTA with a very low likelihood for cardiac events. Two systematic reviews/meta-analyses on the prognostic value of CCTA also confirmed these findings with low cumulative major adverse cardiac events in patients with normal CCTA findings, but much higher event rates in patients with abnormal CCTA showing obstructive CAD.…”
Section: Limitations Of Cctasupporting
confidence: 83%
“…Another study examined the prognostic value of CTA in 218 Patients over a follow-up period of more than 6 years. [70] Images were analyzed for non-obstructive (\50 %) or obstructive (50 % stenosis) CAD, and major adverse cardiovascular events (MACE) were identified, including death, nonfatal myocardial infarction or urgent coronary revascularization. CTA revealed normal coronaries in 49, non-obstructive lesions in 94, and obstructive CAD in 75 patients.…”
Section: Computed Tomography Componentmentioning
confidence: 99%
“…The maximum follow-up time of 7.5 years was unusually long in this context, although the median follow up time of 3.1 years was more in line with earlier studies. Only three patients (0.2%) were lost to follow-up, due to not having a Swedish personal identity number, as compared to approximately 5-15% in several other studies (25,27,28).…”
Section: Study IVmentioning
confidence: 71%
“…All exams in patients with known CAD or other cardiac disease were excluded, as were all exams with suboptimal image quality. Thus, the patient selection process was similar to several other studies with similar objectives (24)(25)(26)(27)(95)(96)(97).…”
Section: Study IVmentioning
confidence: 97%
See 1 more Smart Citation